Modern Benchmarks in Continuous Teacher Training in the European Context: Array - Popa, Doinita (Didactica Danubiensis, 2022)
This article shows some aspects of the concept of on-the-job training, which is a current trend in adult vocational training, driven by the need for human resource development that is increasingly recognized by employing institutions and by the rapid changes imposed by social dynamics.This new trend is justified by the fact that on-the-job training offers employees opportunities to put into practice the skills acquired through other forms of further training. Through on-the-job training, the employee has the advantage of “working, learning and gaining experience at the same time”. Thus internal continuous training offers the possibility of faster training of skills and ensures the transfer of knowledge acquired through learning.